The Portrait of Character Education in Yadnya Enactment Among Hindu Society - Yasa, I Gede Putu (Jurnal Penelitian Agama Hindu, 2023)
In general, ordinary people are of the view that being religious is doing yadnya in the form of a ceremony. In good economic conditions, this will not cause problems, but in declining economic conditions, it will have an impact on decreasing sincerity and sincerity in giving. Thus, it is deemed necessary to instill the concept of religion in accordance with the guidance of the holy books. This study aims to describe character education in the actualization of yadnya in the Traditional Village of Perang, Lukluk Village, Mengwi District, Badung. This study employed a qualitative approach by collecting data from observation, interviews, and literature review. The findings show that an understanding of the three basic frameworks, namely, philosophy/tattwa, moral ethics and yadnya needs to be socialized to the community, especially community leaders such as stakeholders, srati and uperengga who are directly involved in many ceremonial activities. According to the Bhagawad Gita and Veda, yadnya is not only carrying out offering ceremonies, but working, socializing and all activities carried out sincerely for the welfare and peace and happiness of all beings, including yadnya. Thus, when interacting in all things, it is necessary to have ethics/morals in accordance with the basic framework of Hinduism, because character education comes from religious and cultural education in society. Thus, yadnya provides maximum benefits in accordance with the purpose of performing the yadnya, namely, as a form of devotion and gratitude to God Almighty for all His blessings and grace in all things.